Sienkiewicz - interpretacyjne spory (do jubileuszowego roku 1900) = Sienkiewicz - interpretative disputes (up to the jubilee year 1900) - Bujnicki, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Almost at the beginning of Sienkiewicz's career he was thought to be a controversial writer. First controversy appeared in connection with a story entitled "Charcoal Sketches" ["Szkice węglem"] and their fundamental assumptions. Author himself was sure the reaction would be strong but he did not excpect it from positivist critics. Nevertheless, the attack published in "Weekly Review" ["Przegląd Tygodniowy"] met not only Bolesław Prus' but also Aleksander Świętochowski's objections. Such an attitude of the latter towards "Sketches" encouraged Sienkiewicz to another project - writing a series of a similar pamphlet tone, but he resigned from this idea. Next dispute - much broader - aroused because of issuing the first historical novel "With Fire and Sword" ["Ogniem i mieczem"] by Sienkiewicz.
Keywords: pozytywizm; konserwatyzm; powieść historyczna; prawda historyczna; tożsamość; positivism; conservatism; historical novel; historical thrut; identity